Training challenges face by employee in public sectors at the age of globalization : a study conducted on Likas hospital and immigration department / Rabi'atul 'Adawiyah Masdor - Masdor, Rabi`atul `Adawiyah (2010)
The purpose of this study is to know the challenges that face by employees in the public sector in term of training needs. Not just that, this study also been done because the researcher wants to identify and investigate whether training challenges that face by employees in facing the globalization were connected between each other. Further discussion has been made in this research where the objective of this study has been achieved. Apart from that, this research is generally conducted in public sector where there are two organizations that have been chosen by researcher in order to investigate more about this research.